(untitled) (Siddhajyoti Interdisciplinary Journal, 2022)
This article discusses classroom discourse theoretically. English language class consists of talks which occur between teachers and students. It takes place in the area of classroom research to be studied. The language learning is the main concern of the interaction existing in the classroom setting includes linguistic perspective. Additionally, issues of classroom talk in terms of teaching learning of English language formulate the interactive events in the class for meeting the educational goals. Similarly, the classroom activities become managed and balanced through the language is practiced for communicative purposes. Language teaching is associated with the interaction that exists in language learning and communicative aspects. Students and teachers communicate in the respect of course contents. Such teaching learning is linked with language and culture. To the case of this article, theoretical aspect of discourse is focused. In line with the classroom discourse, different elements play role for cultivating the discourse. Language teaching reflects the conversation which takes place regarding the teachers’ facilitation to the learning of language in learning of students. Linguistic perspective visualizes the language used in classroom situation.